Effects of CNT diameter on mechanical properties of aligned CNT sheets and composites. (September 2015) - Nam, Tran Huu; Goto, Ken; Yamaguchi, Yudai; Premalal, E.V.A.; Shimamura, Yoshinobu; Inoue, Yoku; Naito, Kimiyoshi; Ogihara, Shinji
Abstract: Drawing, winding, and pressing techniques were used to produce horizontally aligned carbon nanotube (CNT) sheets from free-standing vertically aligned CNT arrays. The aligned CNT sheets were used to develop aligned CNT/epoxy composites through hot-melt prepreg processing with a vacuum-assisted system. Effects of CNT diameter change on the mechanical properties of aligned CNT sheets and their composites were examined. The reduction of the CNT diameter considerably increased the mechanical properties of the aligned CNT sheets and their composites. The decrease of the CNT diameter along with pressing CNT sheets drastically enhanced the mechanical properties of the CNT sheets and CNT/epoxy composites. Raman spectra measurements showed improvement of the CNT alignment in the pressed CNT/epoxy composites. Research results suggest that aligned CNT/epoxy composites with high strength and stiffness are producible using aligned CNT sheets with smaller-diameter CNTs.